Correlation between the Use of Information and Communication Technology and Teachers’ Job Performance: A Brief Report - Fereidoon Yazdani (Interdisciplinary Journal of Virtual Learning in Medical Sciences)
Various factors can predict teachers' educational performance, one of which is their use of Information and Communication Technology (ICT) tools. The role of these tools in influencing teachers' performance warrants a detailed review. This study investigates the correlation between the use of ICT tools and job performance among elementary school teachers.A descriptive cross-sectional approach was utilized for the methodology. The population included all public elementary school teachers (n=201) in the Sardroud region of Razan City, Iran, from September to November 2023. A total of 132 teachers participated in the study using a random sampling method. Two researcher-made questionnaires were utilized to gather data, each demonstrating a reliability exceeding 0.75. Consequently, the impact of ICT on teachers' job performance across cognitive, emotional, and skill dimensions was assessed.The study's findings indicated a direct and significant correlation between teachers' use of ICT tools in the teaching-learning process of the classroom with their cognitive (r=0.38, p=0.009), emotional (r=0.48, p=0.003) and skill (r=0.46, p=0.003) functions.The research findings indicate that teachers should be encouraged to incorporate ICT tools effectively into the classroom environment to improve their job performance and enhance the overall teaching and learning experience for their students.